Pengaruh Substitusi Tepung Jewawut (Pennisetum Glaucum) pada Butter Cake terhadap Daya Terima Konsumen - Hakimah, Dalilah; Dahlia, Mutiara; Mahdiyah, Mahdiyah (Journal of Law and Social Politics, 2024)
This research aims to study and analyze the effect of jewaut flour substitution in butter cake on consumer acceptance. The study was conducted at the Pastry and Bakery Laboratory, Culinary Education Study Program, Universitas Negeri Jakarta. The research started in September 2021 to february 2024. The method used in this study was an experimental method. The research sample were butter cake with jewawut flour substitution at 20%, 30%, and 40%, than tested on 30 semi trained panelists evaluating various organoleptic aspects. Based on the results of the statistical hypothesis test using the Friedman test, it shows that there are no influence of substituted jewaut flour at 20%, 30%, and 40% in the making of butter cake in volume, color of crumb, softness, pores, butter aroma, aroma of jewawut flour and sweetness aspect. While on the color aspect of the upper surface and the taste of jewawut flour there is a significant differece in butter cake substitute with jewawut flour. Based on the results of the statistical hypothesis test, the physical quality test using the Anova test showed that the aspects of swellability had no significant effect or difference in the substitution of jewawut flour at 20%, 30%, and 40% in the manufacture of butter cake. The conclusion of this study is to recommend butter cake with 30% jewawut flour substitution to be developed in optimizing the use of jewawut flour as a functional local food.